Fostering Inclusive & Adaptive Behavior of Inmates: The Role of Multicultural Islamic Education in Surabaya’s Class 1 Correctional Institution - Aprilita Hajar; Maskuri; Abdul Jalil; Chairil Anwar (Universitas Islam Negeri Ar-Raniry, 2026)
Abstract This study examines how multicultural Islamic education contributes to the development of inclusive adaptive behavior and active religious engagement among inmates at a Class I Correctional Institution in Surabaya. Prisons represent complex multicultural environments marked by diverse religious, cultural, and social backgrounds that often generate tension and exclusion. Positioned within the discourse of multicultural education and rehabilitative correctional practices, this research adopts a qualitative phenomenological approach to explore inmates’ lived experiences. Data were collected through in-depth interviews, participant and non-participant observations, and analysis of institutional religious and social programs, and were analyzed thematically. The findings reveal that inclusive behavior is fostered through role modeling by religious leaders, correctional officers, and senior inmates, as well as through routine religious, social, and vocational activities that emphasize empathy, tolerance, cooperation, and social responsibility. Moreover, inmates’ re-engagement in religious roles such as mentoring peers, leading prayers, teaching Qur’an, and delivering sermons strengthens leadership, moral awareness, and social solidarity. These processes facilitate spiritual growth and enhance inmates’ readiness for social reintegration. The study demonstrates that integrating Islamic multicultural values into correctional education can serve as an effective strategy for inclusive rehabilitation in multicultural institutional settings.